Perfil químico e volátil de vinhos espumantes secos e meio doces do Vale do São Francisco - Ledo, Luan Victor Rodrigues (2019)
Currently, grape cultivation in Brazil is done in several localities, mainly South, Southeast and Northeast regions. In Southern and Southeastern regions. The vine is cultivated with one productive cycle per year, due to the conditions of temperate and sub-humid subtropical climates, respectively, where the vine goes through the rest period in winter low temperatures. In the Submédio São Francisco Valley, located between the 8-9º parallels of the Southern Hemisphere, climate is tropical semi-arid, whose soil and climatic characteristics make it possible to stagger the production of table grapes, wines and grape juice throughout the year. Differently of South and Southeast regions, a vine plant can produce two harvests per year, due to high temperatures, solar radiation and water availability in abundance for irrigation. In this study, six samples of brut and demi-sec sparkling wines obtained from two wineries in São Francisco Valley, and two samples of sparkling wines produced in Serra Gaúcha, commercially available, were analyzed for the determination of their physicochemical characteristics and volatile compounds. Volatile compounds analysis was made by GC-MS, using the HS-SPME extraction method. Sixty-nine volatile compounds were identified, mainly esters, alcohols and terpenes. The sparkling wines of the VSF and the South exhibited variations in physicochemical composition and the volatile profile. The main compounds that characterized brut and démi-secs sparkling wines of São Francisco Valley were esters, terpenes and alcohols, wines from the South of Brazil were characterized by other esters, terpenes and alcohols as well. Analysis of the main components of physicochemical attributes differentiated the sparkling wines by type, brut and semi-sweet, and the analysis of volatiles differentiated them by the winery. The winery A presented the highest number of volatile compounds found in its sparkling wines while the sparkling wines of the B wine cellars had the lowest amount of volatile compounds.